Allocation of Losses and Costs of the Transmission System within a Unregulated Environment - Castillo Correa, Carlos Gilmer (2020)
The electric transmission system is the infrastructure that allows the transfer of energy from the production points to the consumption centers. It has the characteristic of regulated natural monopoly. For efficiency and economic equity in the electricity market, it is necessary that both the electrical losses and the costs incurred in the transmission process be properly distributed among all the agents that make use of this system. That is why around the world a series of methodologies have been developed that allow the regulators of the electrical system to set the transmission rates that assure their owners to recover the costs incurred in the construction, operation and maintenance and allow the efficient development of the Long-term network. In this context, this article reviews the different methodologies for assigning electrical losses and transmission costs at national and international level.